2019
DOI: 10.29271/jcpsp.2019.03.210
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of Dental Midline with Facial Midline in a Sample of Pakistani Population

Abstract: Objective: To determine the frequency of coincidence of facial and dental midlines in a sample of Pakistani subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Only 9.33% of total subjects (6.66% of male and 12% of female), had perfectly coinciding facial midlines with maxillary midline. In contrast 47.9% of Pakistani population 14 ,72.5% of Karnataka population 11 and 85% of Caucasian 15 had facial and maxillary dental midline coinciding. All of those studies considered only one parameter as facial midline which was similar to F2 facial midline of this present study.…”
Section: Discussionmentioning
confidence: 87%
“…Only 9.33% of total subjects (6.66% of male and 12% of female), had perfectly coinciding facial midlines with maxillary midline. In contrast 47.9% of Pakistani population 14 ,72.5% of Karnataka population 11 and 85% of Caucasian 15 had facial and maxillary dental midline coinciding. All of those studies considered only one parameter as facial midline which was similar to F2 facial midline of this present study.…”
Section: Discussionmentioning
confidence: 87%
“…But a small axial midline angulation (10°) is already easily noticeable. Furthermore, Khan et al [15] studied the dento-facial midline in Pakistani subjects and they found that the upper midline was coinciding with lower midline only in 2/3 rd of the subjects and facial midline was coinciding with the dental midlines in <50% of the subjects. But they found that dental midline deviations were more on the left side which was contrast to our study.…”
Section: Discussionmentioning
confidence: 99%
“…But a small axial midline angulation (10°) is already easily noticeable. Furthermore, Khan et al [15] studied the dento-facial midline in Pakistani subjects, and they found that the upper midline was coinciding with the lower midline only in 2/3 rd of the subjects and facial midline was coinciding with the dental midlines in <50% of the subjects. But they found that dental midline deviations were more on the left side, which was in contrast to our study.…”
Section: Discussionmentioning
confidence: 99%